2021
DOI: 10.3390/ijerph19010155
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Seawater Intrusion in Coastal Aquifers Using Multivariate Statistical Analyses and Hydrochemical Facies Evolution-Based Model

Abstract: Groundwater (GW) studies have been conducted worldwide with regard to several pressures, including climate change, seawater intrusion, and water overexploitation. GW quality is a very important sector for several countries in the world, in particular for Tunisia. The shallow coastal aquifer of Sfax (located in Tunisia) was found to be under the combined conditions of continuous drop in GW and further deterioration of the groundwater quality (GWQ). This study was conducted to identify the processes that control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 55 publications
(77 reference statements)
0
14
0
Order By: Relevance
“…SWI is identified by the anion and cation percentage distribution in the square diagram. Subsequently, the HFE-D model has been utilized in several studies to identify the SWI phase in coastal aquifers worldwide (e.g., [ 47 , 49 ]). We used the Excel macro published by [ 50 ] to establish the HFE-D model for the tested GW samples from both aquifers in the study area, as shown in Figure 10 .…”
Section: Resultsmentioning
confidence: 99%
“…SWI is identified by the anion and cation percentage distribution in the square diagram. Subsequently, the HFE-D model has been utilized in several studies to identify the SWI phase in coastal aquifers worldwide (e.g., [ 47 , 49 ]). We used the Excel macro published by [ 50 ] to establish the HFE-D model for the tested GW samples from both aquifers in the study area, as shown in Figure 10 .…”
Section: Resultsmentioning
confidence: 99%
“…(Chosen were the clastic-sedimentary regional aquifers: the Piney Point (NACPPAS1A) and Potomac (NACPPAS1B and NACPPAS2B); see Table SI.1.) The first four principal components (PCs) of the PCA model for the NACP PA were chosen as grouping surrogates for the geochemical environment and water type in accordance with similar analyses in other Coastal Plain aquifers. , …”
Section: Materials and Methodsmentioning
confidence: 99%
“…(Chosen were the clastic-sedimentary regional aquifers: the Piney Point (NACPPAS1A) and Potomac (NACPPAS1B and NACPPAS2B); see Table SI environment and water type in accordance with similar analyses in other Coastal Plain aquifers. 43,44 Detailed descriptions of the geochemical model methods and results are given in the Supporting Information. The geochemical models were used to identify reasonable geochemical processes that could account for the evolution of the different geochemical environments regionally allowing for classification of water types associated with the high 226 Ra and 210 Po concentrations.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The most common mapping methods in the groundwater sector are IDW and kriging interpolation. According to several earlier researches (Hajji et al, 2022;Yang et al, 2020;Zolekar et al, 2021), the IDW interpolation method is more accurate than the Kriging tool. Additionally, IDW has a track record of being easy to use, quick, and produces accurate results (K. X.…”
Section: Sampling and Chemical Analysismentioning
confidence: 99%